2015
DOI: 10.1371/journal.pone.0118608
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Direction of Change of Cerebral Function Parameters Are Evident over Three Years in HIV-Infected Individuals Electively Commencing Initial cART

Abstract: BackgroundChanges in cerebral metabolite ratios (CMR) measured on 1H-MRS and changes in cognitive function (CF) are described in subjects commencing combination antiretroviral therapy (cART), although the dynamics of such changes are poorly understood.MethodsNeuroasymptomatic, HIV-infected subjects electively commencing cART were eligible. CMR were assessed in three anatomical voxels and CF assessed at baseline, week 48 and week 144. Overall differences in absolute change in CMRs and CF parameters between 0–48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This finding may reflect that ANI indeed represents a mild level of HIV brain involvement. It could also reveal that DTI FA and MD measures may not be the most sensitive to ongoing brain injury that have been shown using CSF analyses (Jessen Krut et al 2014) and 1 H-MRS (Cysique et al 2013;Winston et al 2015) in virally suppressed and ANI patients. The WM alterations were more widespread in the MND + HAD consistent with the greater severity of the underlying HIV brain involvement (major association fibers, EC, FX, and CG, for both MD and FA suggesting both atrophy and axonal injury).…”
Section: Discussionmentioning
confidence: 97%
“…This finding may reflect that ANI indeed represents a mild level of HIV brain involvement. It could also reveal that DTI FA and MD measures may not be the most sensitive to ongoing brain injury that have been shown using CSF analyses (Jessen Krut et al 2014) and 1 H-MRS (Cysique et al 2013;Winston et al 2015) in virally suppressed and ANI patients. The WM alterations were more widespread in the MND + HAD consistent with the greater severity of the underlying HIV brain involvement (major association fibers, EC, FX, and CG, for both MD and FA suggesting both atrophy and axonal injury).…”
Section: Discussionmentioning
confidence: 97%
“…Composite scores for sleep questionnaires were calculated and interpreted as per questionnaire protocols and cutoffs (table 1). Neurocognitive scores were analysed using Cogstate® recommendations [35]. Statistical analyses were performed using Stata (version 14.1) and GraphPad Prism (version 7.03).…”
Section: Sleep and Cognitive Data Analysismentioning
confidence: 99%
“…Similarly, in the ALTAIR study speed and accuracy domains improved over the first year after cART initiation with no individual domain showing deterioration from baseline at week 48 [ 7 ]. However, in the long term follow up of this study a decline in global cognitive function score was observed over 144 weeks and the authors hypothesised this could be related to antiretroviral toxicities [ 12 ]. In our study, domains critically affected in HIV-associated cognitive impairment such as detection and identification times [ 13 ] deteriorated slightly at week 48 after an initial improvement at week 24 (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%